Interfaith Educational Collaboration Enhances Cultural Adaptation in Lombok and Bali - Fathurrahman Muhtar; Nasir, Mohamad Abdun; Sudarsono; Hasniza Nordin (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study explores the collaborative role of religious educators in fostering interfaith harmony in Lombok and Bali, regions with diverse religious demographics. Design/methods/approach – A mixed-methods approach was used, combining qualitative case studies and quantitative analysis. Data were collected through interviews, observations, document analysis, and a Likert-scale questionnaire administered to 170 students. Structural equation modeling (PLS-SEM) assessed relationships between perception, interaction experience, attitude, and understanding. Findings – Perception significantly influences interaction experience (0.930) and understanding (0.464), while interaction experience directly enhances understanding (0.505). Attitude had minimal impact (0.013). The model showed high predictive accuracy, with R² values of 90.2% for understanding and 84.9% for interaction experience, highlighting the importance of fostering positive perceptions and engagement. Research implications/limitations – The study focuses on two regions, limiting generalizability. Further research should explore long-term impacts and broader applications in multicultural settings. Originality/value – This study provides empirical evidence of interfaith collaboration's effectiveness in education, contributing valuable insights into religious inclusivity and social integration. Future research could expand this framework to other cultural contexts.